Clicker Training in Minipigs to Reduce Stress during Blood Collection—An Example of Applied Refinement - Delia Fiderer; Christa Thoene-Reineke; Mechthild Wiegard (Animals)
Pigs (and minipigs) are often restrained with a maxillary sling for blood collection. They mainly produce strong vocalisations and show resistance to the procedure, which subjectively appears to be stressful for the animals. The present study investigated whether minipigs can be trained to tolerate aversive stimuli and whether training can reduce stress during blood collection. Blood was taken from 12 Ellegaard minipigs with fixation; thereafter, the animals were trained for 3 weeks using clicker training. Then, blood was taken again, but without fixation. Before and after each blood sample, saliva samples were taken. The cortisol concentration was determined using ELISAs. Serum cortisol was not significantly different before and after training (paired-sample t-test, t (9) = 2.052, p = 0.07). However, salivary cortisol was significantly lower after training (ANOVA (analysis of variance), p-value < 0.001, F-value 6.181). In addition, trained minipigs showed a significantly lower heart rate after blood sampling (paired-sample t-test, t (11) = 4.678, p = 0.001) as well as significantly lower heart rate variability (t (11) = 3.704, p = 0.003) compared to before training. The minipigs could be trained to tolerate aversive stimuli. This contributed to stress reduction when taking blood samples.